Investigation of the effect of breast milk, probiotic supplemented and plain milk formulas on some oral bacteria in infants: an observational and in-vitro study - Elazim, Mariam Mohamed Abd; Kabil, Noha Samir; Wassel, Mariem Osama; Nasser, Marwa Shaaban (Brazilian Dental Science, 2022)
Objective: inconclusive evidence exists regarding potential cariogenicity of milk formulas compared to breast milk.The study aimed to compare Salivary Streptococcus mutans (S. mutans) and lactobacilli detection and counts amongbreastfed (B), plain formula (France Lait 1) (FL) and probiotic supplemented formula (Nan 1 optipro) (N) infantsand to assess in-vitro growth of these bacteria in breast milk and milk formula samples. Material and Methods:salivary samples were obtained using sterile cotton swabs from 60 infants that were grouped according to nursingmilk type. Samples were cultured to obtain the detection frequency and bacterial counts. For the in-vitro investigation,seven donated breast milk samples and seven freshly prepared samples of both milk formulas were inoculated byboth bacteria and then cultured to assess bacterial growth. Results: lactobacilli were detected in all infants, whileno significant differences were found in S. mutans detection among groups. Counts of both microorganisms insaliva were lowest in (B) while, insignificant difference was found between (B) and (N). Significant differenceswere evident in in-vitro bacterial counts being lowest in (B) followed by (N) and (FL). Conclusion: breast milk andprobiotic supplement infants’ milk formulas may have a protective role against dental caries in infants.KEYWORDSBreast milk; Lactobacilli; Milk formula; Probiotics; Streptoccus mutans.